HIGH POWER SHORT DURATION VS LOW POWER LONG DURATION CATHETER ABLATION OF ATRIAL FIBRILLATION - Rheinhardo Lolonlun, Titus; Christian Fernandez, Daniel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Backgrounds : Atrial Fibrillation (AF) is a known common arrythmia, affecting around 33 million people worldwide. Catheter ablation is a safe and effective treatment for paroxysmal and persistent AF that are unresponsive to drug treatment. However, long procedural duration of AF ablation has raised the concern of radiation hazard and post-procedural complications. The high power short duration (HPSD) technique is an emerging method that has been introduced as an alternative to reduce procedural time of AF ablation. Objective: This study attempts to review the safety and efficacy of HSPD compared to the conventional low power long duration (LPLD) ablation in AF patients.Method : A search through PubMed, Science Direct, JSTORE, and clinicaltrial.gov was conducted. The keywords used were (catheter ablation OR radiofrequency OR pulmonary vein isolation) AND (atrial fibrillation) AND (high power short duration OR 50 W). The search was limited from 2006 to 2024. Risk of bias assessment was conducted through Newcastle-Ottawa Scale (NOS) assessment. Results: Among 55,802 journals reviewed, we retrieved 10 journals that met the inclusion criteria. This study found that HPSD ablation results in either better or comparable efficacy in maintaining long term sinus rhythm post ablation. Additionally, there was no difference in safety for both HPSD and LPLD. We also recommend using esophageal temperature monitoring probe and adjusting energy delivery during posterior wall ablation to avoid injuring esophagus.Conclusion: Our study concluded that HPSD ablation is a safe choice of treatment for drug-refractory paroxysmal or persistent AF with a noteworthy outcome compared to LPLD ablation.